Crestal Approach to Sinus Floor Elevation for Atrophic Maxilla Using Platelet-Rich Fibrin as the Only Grafting Material: A 1-Year Prospective Study. Issue 1 (February 2016) - Kanayama, Takeo; Horii, Koichiro; Senga, Yasuko; Shibuya, Yasuyuki
Abstract : Purpose: Platelet-rich fibrin (PRF) has been recently used as the sole grafting material in sinus floor elevation procedures. The aim of this prospective study was to measure the bone gain around the dental implant after using the crestal approach to sinus floor elevation using platelet-rich fibrin as the only grafting material in atrophic posterior maxillae with residual bone height <5 mm. Materials and Methods: Two different types of implants were used: hydroxyapatite (HA) and sandblasted acid-etched (SA) implants. Panoramic radiography and computed tomography were used to measure the endosinus bone gain. Results: Twenty-seven patients with 39 implants (19 HA and 20 SA) were included in this study. The mean residual bone measurements before surgery in the SA and HA groups were 2.85 and 2.68 mm, respectively. The mean average bone gains for 1 year in the SA and HA groups were 4.38 and 4.00 mm, respectively. Conclusion: This prospective study showed that platelet-rich fibrin promoted endosinus bone gain when used as the grafting material in the crestal approach to sinus floor elevation.